The therapeutic roles of etanercept and thalidomide in bleomycin induced experimental scleroderma - Isik, A.; Koca, S.; Evren, B.; Ustundag, B.; Ozercan, I.; Metin, K. (B M J Publishing Group, 2007)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2007) -- JUN 13-16, 2007 -- Barcelona, SPAIN
Keywords: Necrosis-Factor-Alpha